Efforts to Improve The Sustainability of Traditional Food Sales At Funny's Kitchen, Bandung: Upaya Meningkatkan Keberlanjutan Penjualan Makanan Tradisional di Funny’s Kitchen, Bandung - Talar, Yulianti; Wirawan, Christina; Sandroto, Indah Victoria; Gozaly, Jimmy; Hermawan, Melina; Dongu, Yulia Pratama Umbu (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Funny's Kitchen is one of the tenants of Foodcourt E at X University. Internal improvements were carried out based on research on students as the main consumers of Funny's Kitchen. The results of Multiple Linear Regression processing from 99 students' data show that the freshness of the food, the suitability of the price to the quality of the food provided, and the correct temperature of the food provided have a significant effect on students' interest in repurchasing at Funny's Kitchen. It is proposed that Funny's Kitchen use a microwave to speed up the process of heating food, maintain the taste of the food, employ employees who can help with the process of preparing and serving food, and adjust prices to the quality of the food provided. In this PKM, training was carried out to calculate the cost of production and it was discovered that Funny's Kitchen could still increase the quantity of its food portions. It is hoped that through the improvements made, student interest in buying back traditional food at Funny's Kitchen can increase.